Management of Meloidogyne incognita by using Different Extract Forms of Acorus calamus - and L. Joymati Devi2, N. Romabati Devi1* , Kh. Solitary Devi1 (Journal of Experimental Sciences, 2011)
The effect of different extract form of Acorus calamus L. were tested against second stage larvae of Moloidogyne incognita. Hundred percent larval mortality were found with aqueous extracts of rhizome of A. calamus at 5 and 10 percent concentration in 96 and 72 hours of treatments. At dry powder form of the rhizome cent percent larval mortality was found at 10 percent concentration in 120 hours exposure period. The oil extract of rhizome also caused significant mortality of the larvae at 500 ppm and 300 ppm.